A certificateless Multi-receiver Encryption scheme based on SM2 signature algorithm - Jinglin Zou; Debiao He; Sheng Bi; Libing Wu; Zhe Liu; Cong Peng (High-Confidence Computing, 2023)
The Multi-receiver Encryption (MRE) scheme can meet the secure data transmission requirements in multicast and broadcast scenarios. To meet compliance, critical information infrastructure in China should be protected with Chinese national commercial cryptographic algorithms. Designing an MRE scheme based on Elliptic Curve Cryptography (ECC) is one of the current design methods with better flexibility and performance. However, the research on MRE schemes based on SM2 elliptic curve public-key cryptography is still in a blank state. This paper proposes a Certificateless SM2-based Multi-receiver Encryption (CL-SM2-MRE) scheme. We prove the security of the CL-SM2-MRE scheme under the Random Oracle Model (ROM) and analyze the performance.